PTU-141 A study of variceal bleeding across continents. (8th June 2018) - Walker, Tom; McIntosh, Stuart; Vijayan, Balasubramaniam; Fraser, Andrew
Abstract : Introduction: The underlying aetiology and subsequent management of variceal haemorrhages is well documented in developed countries however, there is significantly less data from developing countries. The aim of this study was to compare the aetiology and management of patients presenting with variceal haemorrhage to Aberdeen Royal Infirmary (ARI) and its allied Felege Hiwot Referral Hospital (FHRH), Ethiopia. Methods: Two medical students spent their electives performing retrospective case note reviews of all patients presenting with variceal haemorrhage to FHRH between September 2013 and September 2015 and ARI in a similar time period between January 2013 and December 2015. Patients were identified from the Ward Register. Case notes were examined for patient demographics, symptoms, investigations, management and mortality data. Results: There were 66 patients presenting to FHRH and 129 patients presenting to ARI during the study period. Mean age at presentation was 37.7 (FHRH) and 57.4 (ARI). Aetiology of liver disease was significantly different between the 2 sites. At FHRH Schistosomiasis accounted for (33.3%), Hepatitis C (24.6%) and Hepatitis B (22.8%). At ARI, the most common aetiology was alcohol related liver disease (58.9%) followed by non-alcoholic fatty liver disease (14.7%). Conclusions: The underlying aetiology of liver disease resulting in portal hypertension and variceal haemorrhage is very different in the 2 hospitals studied. The management is also significantly different due in part to the resources available. Unfortunately admission haemodynamic data and Haemoglobin measurements were not reliably recorded for comparison. Clinical management of patients presenting with variceal haemorrhage at FHRH does not follow as stringent a protocol as ARI which is likely to explain the higher rates of blood transfusions required in FHRH. Although these data suggests that fewer patients at FHRH represent with variceal bleeding over a 2 year period, many patients in the area cannot afford to attend hospital repeatedly resulting in under-reporting of cases. There is an ongoing knowledge exchange between University of Aberdeen and Bahir Dar University which will hopefully improve the access to appropriate educational and training resources to reduce the variability between the 2 centres